2013
DOI: 10.1124/dmd.113.055988
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Human Arylamine N-Acetyltransferase 1 with Different Nanomaterials

Abstract: Humans are exposed to nanoparticles in the environment as well as those in nanomaterials developed for biomedical applications. However, the safety and biologic effects of many nanoparticles remain to be elucidated. Over the past decade, our understanding of the interaction of proteins with various nanomaterials has grown. The protein corona can determine not only how nanoparticles interact with cells but also their biologic effects and toxicity. In this study, we describe the effects that several different cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…To date, panoply of diverse sulphydryl reactive compounds has been used as irreversible inhibitors of mammalian NATs, only to elucidate the involvement of a Cys residue in the catalytic mechanism of NATs 39 51 52 53 54 55 or propose hypotheses for the putative endogenous role of human NATs 56 57 58 . Other recent studies have also shown irreversible inhibition of human NAT isoforms by different heavy metals 59 60 , and some of the oxidizing products resulting from the oxidation metabolism of aromatic amines 61 . The eventuality that apocynin could act as covalent inhibitor of NAT enzymes would have offered some advantages in drug design, since specific covalent inhibitors are usually associated with lower doses and a longer duration of action, and avoiding resistance 62 .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…To date, panoply of diverse sulphydryl reactive compounds has been used as irreversible inhibitors of mammalian NATs, only to elucidate the involvement of a Cys residue in the catalytic mechanism of NATs 39 51 52 53 54 55 or propose hypotheses for the putative endogenous role of human NATs 56 57 58 . Other recent studies have also shown irreversible inhibition of human NAT isoforms by different heavy metals 59 60 , and some of the oxidizing products resulting from the oxidation metabolism of aromatic amines 61 . The eventuality that apocynin could act as covalent inhibitor of NAT enzymes would have offered some advantages in drug design, since specific covalent inhibitors are usually associated with lower doses and a longer duration of action, and avoiding resistance 62 .…”
Section: Resultsmentioning
confidence: 91%
“…Other recent studies have also shown irreversible inhibition of human NAT isoforms by different heavy metals5960, and some of the oxidizing products resulting from the oxidation metabolism of aromatic amines61. The eventuality that apocynin could act as covalent inhibitor of NAT enzymes would have offered some advantages in drug design, since specific covalent inhibitors are usually associated with lower doses and a longer duration of action, and avoiding resistance62.…”
Section: Resultsmentioning
confidence: 99%
“…The mode of inhibition in this case involves the binding of the NM to the active site of NAT1, thus preventing NAT1 from binding to the target substrate. Interestingly, the more negative the surface charge of the NM, the lower the LD50 concentration needed to inhibit the NAT1 activity, highlighting the importance of considering NM charge as a critical design parameter to inhibit enzymatic activity …”
Section: Some New Yin and Yang Relationships Of Nms With Biological Pmentioning
confidence: 99%
“…Interaction of nanomaterials with proteins essential for cellular functions could inactivate them either by conformational changes and/or denaturation. Both CB and TiO 2 nanoparticles were shown to inhibit enzyme activity and induce conformational changes in Arylamine N-Acetyletransferase-1 44,45 , a xenobiotic metabolizing enzyme involved in activation/detoxification of carcinogens. Although in this case both nanomaterials induce similar effects, the magnitude of the response varies hugely.…”
Section: Consequences Of the Interaction Of Nanomaterials With Proteinsmentioning
confidence: 99%